2006
DOI: 10.1002/cncr.21720
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance‐guided, vacuum‐assisted breast biopsy

Abstract: BACKGROUNDThe objective of this study was to determine the accuracy, reproducibility, and clinical value of magnetic resonance (MR)‐guided, vacuum‐assisted breast biopsy (MR‐VAB) in a prospective, multicenter study.METHODSIn 5 European centers, MR‐VAB was performed or attempted on 538 suspicious lesions that were visible or could targeted only by MR imaging (MRI). Verification of malignant or borderline lesions included reexcision of the biopsy cavity. Benign biopsy results were verified by retrospective corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
2
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(37 citation statements)
references
References 25 publications
3
30
2
2
Order By: Relevance
“…However, because the percentage of malignant cases will vary by differences in reporting methods, as well as the prevalence of cancer in patients evaluated with MRI, the most accurate comparisons of biopsy technologies are determined by comparison of underestimation rates and complications. The EnCor device, with an underestimation rate of 7% (4/55), compares favorably with previous reports, ranging from 2%-8% (22)(23)(24)(25)(26)(27). The complication rate of 4% is also comparable to previous reports, ranging from 0%-10% (22)(23)(24)(25)(26)(27).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, because the percentage of malignant cases will vary by differences in reporting methods, as well as the prevalence of cancer in patients evaluated with MRI, the most accurate comparisons of biopsy technologies are determined by comparison of underestimation rates and complications. The EnCor device, with an underestimation rate of 7% (4/55), compares favorably with previous reports, ranging from 2%-8% (22)(23)(24)(25)(26)(27). The complication rate of 4% is also comparable to previous reports, ranging from 0%-10% (22)(23)(24)(25)(26)(27).…”
Section: Discussionsupporting
confidence: 84%
“…The number of underestimates identified at follow-up surgery or imaging was not reported (Table 5). Perlet et al (21,22) reported interim results of a prospective, multicenter study of MR-guided breast biopsy in 2002, and published the final results in 2006. As with the study reported by Viehweg et al, an adaptation of the original stereotactic Mammotome was used to perform the MRI-guided biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, a benign diagnosis was made in 55-70% of lesions that underwent MRI-guided biopsy. [32][33][34] On the other hand, lesions evaluated in this study represent a high-risk group for malignancy, which may explain the low rate of biopsies with negative findings.…”
Section: Discussionmentioning
confidence: 81%
“…MRI-guided vacuum-assisted core needle biopsy (MRVAB) is fast, safe, and provides large tissue samples for histopathological evaluation. The cancer detection rates using MRI-guided breast biopsy varies considerably, from 18% to 61%, in the published literature [17-21]. This variation can be explained by significant differences in study design and patient population.…”
Section: Introductionmentioning
confidence: 99%
“…The terms “upgrade to malignancy” and “underestimation of malignancy” have been used interchangeably in the literature for lesions that were diagnosed as high risk lesions at biopsy, but with final pathology at excision changed to malignancy (in situ or invasive), as well as for in situ lesions at biopsy upstaged to invasive cancer at surgery [17-21]. The term “upgrade rate to malignancy” was used in our study to define frequency of upgrading of benign and high risk lesions at MRVAB (false negative cases) to malignancy, as well as upstaging in situ MRVAB lesions (true positive cases) to invasive cancer according to final histopathology at surgery.…”
Section: Introductionmentioning
confidence: 99%